Effectiveness of Sales and Operational Audits at PT. Angkasa Pura II - Hendra Saputra; Ayu Kurnia Sari (Ridwan Institute, 2023)
Functional review is an administrative tool defined to reduce the occurrence of misuse of assets. The Functional Review process begins with an examination of the presence of exercises, as well as distinguishing areas of positive improvement and then creating measurable execution norms for an action. An organization has a favor or item to be promoted. A deal is an administrative or merchandise exchange interaction delivered by an organization. The motivation behind this exploration is to show observationally that the Functional Review affects the Adequacy of Expanding Agreement of PT. Angkasa Pura II. Exploration This examination is a quantitative exploration. Consequences of this study This study has no impact between past exploration factors that exert a very large impact. carried out can achieve the goals that have been set. This examination has no impact on the organizational reasons of PT. Angkasa Pura II Silangit Branch does not sell shares, so this organization is a subsidiary organization